Divergent seasonal dynamics of high-resolution phosphorus speciation in sediment porewater of small estuaries - Yeran Yin; Hanchang Zhou; Yurui Li; Zheng Wang; Kai Xiao; Zhanrong Guo; Feng Pan; Bojie Fu (Journal of Hydrology, 2026)

Composite copula adaptive metropolis for joint parameter estimation in hydrological models - Feng Wang; Guohe Huang; Yurui Fan; Yongping Li; Zhenyao Shen; Ya Zhou (Journal of Hydrology, 2026)

Effects of salinity on speciation and mobility of potentially toxic elements in soil porewater of estuarine wetlands - Zheng Wang; Yurui Li; Hanchang Zhou; Chao Li; Yu Cai; Kai Xiao; Zhanrong Guo; Feng Pan (CATENA, 2026)

Contrasting mobility of phosphorus and arsenic in sediments of small estuaries: Insight into high-resolution profiles and seasonal variation - Jiahui Hu; Hanchang Zhou; Zheng Wang; Yurui Li; Kai Xiao; Zhanrong Guo; Feng Pan (Marine Pollution Bulletin, 2026)

Comprehensive phylogenomic analyses of ciliated protists with a revised classification of the phylum Ciliophora (Eukaryota, Alveolata) - Yurui Wang; Ying Yan; Zhenzhen Yi; Yan Zhao; Qianqian Zhang; Yong Chi; Tengyue Zhang; Weiwei Liu; Mingjian Liu; Borong Lu; Mingzhen Ma; Wenbao Zhuang; et al. (Science China Life Sciences, 2026)

A pH/ROS dual-responsive hydrogel enabling a therapeutic trinity of anti-oxidation, anti-inflammation & anti-fibrosis for myocardial infarction repair - Jiao Zhou; Lingbing Zou; Zi Ye; Weiwei Jiang; Jianyu Zheng; Yurui Deng; Linhong Sun; Beibei Guo; Sizhen Wang; Feifei Dong; Feng Yang (Chemical Engineering Journal, 2026)

Mechanistic insight into impacts of Cl− and Br− at high contents on phenol degradation and halogenated by-product formation in O3/H2O2 process - Bing Yang; Shijie Zhou; Xiangfu Huang; Qiang Zhou; Qinchuan Xu; Ying Qiu; Yurui Li; Mengnuo Wang; Yu Wang; Yuming Zhang; Mingyan Chen; Lili Ma; et al. (Process Safety and Environmental Protection, 2026)

Oxidizing agents alter surface reaction pathways in heterogeneous Fenton reactions: Surface electron transfer interactions and altered bond breaking processes in contaminants - Yurui Li; Haoran Wu; Bing Yang; Chao Zhu; Shijie Zhou; Lili Ma; Lingli Li; Mingyan Chen; Heng Guo; Yucheng Liu (Journal of Environmental Chemical Engineering, 2025)

B-Mg co-substituted binder-free ZSM-5 zeolites with recrystallized cheese-like hierarchical porosity for enhanced benzene-methanol alkylation: Synergistic micro-meso-macroporous mass transfer and acid-site engineering - Run Cai; Likun Wen; Yihua Cao; Yindan Wu; Yichen Song; Xinyu Wang; Hanyang Zhou; Yurui Zhang; Xiaoping Dai; Xin Zhang (Chemical Engineering Journal, 2025)

Electrostatic spinning construction of GA/HP-β-CD functionalized COS/PLA composite membrane for cherry tomato preservation applications - Wenge Yang; Jiaxing Hao; Yurui Wu; Yuheng Zhou; Li Mi; Yonghong Hu (Food Packaging and Shelf Life, 2025)

PCL/soy peptide nanofibers incorporated with riboflavin/HP-β-CD assemblies for improving fruit storage quality - Wenge Yang; Aili Wang; Yurui Wu; Yuheng Zhou; Yonghong Hu (Food Chemistry, 2025)

Unveiling the neglected impacts of halide ions on phenol removal in UV/H2O2 system: Light shielding and oxidant utilization efficiency - Bing Yang; Ying Qiu; Qiuping Luo; Xiangfu Huang; Yurui Li; Shijie Zhou; Mengnuo Wang; Mingyan Chen; Lili Ma; Lingli Li; Yucheng Liu (Journal of Water Process Engineering, 2025)

Advances in modified zero-valent iron materials: Synthesis methods, field studies, practical applications and challenges - Yurui Li; Shijie Zhou; Yuan Meng; Ying Qiu; Mingyan Chen; Lili Ma; Lingli Li; Yucheng Liu; Bing Yang (Chemical Engineering Journal, 2024)

Unveiling the kinetics and mechanism of sulfide-modified zero-valent iron activated hydrogen peroxide for phenol degradation - Bing Yang; Yurui Li; Yuan Meng; Ying Qiu; Mi Zhou; Shijie Zhou; Mengnuo Wang; Mingyan Chen; Lili Ma; Lingli Li; Yucheng Liu (Journal of Environmental Chemical Engineering, 2024)

Mechanical protein polycystin-1 directly regulates osteoclastogenesis and bone resorption - Mei Huang; Jingxuan Zhou; Xiaoxiao Li; Ran Liu; Yangzi Jiang; Kaixuan Chen; Yurui Jiao; Xin Yin; Ling Liu; Yuchen Sun; Weishan Wang; Ye Xiao; et al. (Science Bulletin, 2024)

Experimental study on environmental chemical effect and purification treatment of waste slurry in horizontal directional drilling - Pinghe Sun; YuRui He; Shengwei Zhou; Habiyakare Erneste; Qiang Gao; Zihao Zou; Junyi Zhu (Tunnelling and Underground Space Technology, 2024)

Molecular oxygen activation: Innovative techniques for environmental remediation - Lili Zhou; Yuting Liu; Hao Shi; Yurui Qing; Cheng Chen; Liguo Shen; Mingzhu Zhou; Bisheng Li; Hongjun Lin (Water Research, 2024)

Rutin hydrate relieves neuroinflammation in zebrafish models: Involvement of NF-κB pathway as a central network - Ying Hu; Kun Jia; Yatong Zhou; Lixin Chen; Fei Wang; Xiaokun Yi; Yong Huang; Yurui Ge; Xiaomei Chen; Dalong Liao; Yuyang Peng; Yunlong Meng; et al. (Fish & Shellfish Immunology, 2023)

Cloning and Expression of Sox2 and Sox9 in Embryonic and Gonadal Development of Lutraria sieboldii - Min Lu; Zenghou Xing; Yurui Zhou; Youhou Xu; Huijing Peng; Jie Zou; Solomon Felix Dan; Zhicai She; Pengliang Wang; Jinfeng Liu; Shaomin Qin; Jialin Yang; et al. (Fishes, 2022)
The Sox family plays essential roles as transcription factors in vertebrates; however, little is known about the Sox family in Lutraria sieboldii. L. sieboldii are pleasant to eat with a short growth cycle and have become one of the best bottom-seeded enrichment species in Guang Xi. In this study, Sox2 (named LsSox2) and Sox9 (named LsSox9) from L. sieboldii were cloned, and their expression patterns were analyzed. The length of the LsSox2 gene coding sequence was 1011 bp, encoding 336 amino acids, and LsSox9 was 1449 bp, encoding 482 amino acids. LsSox2 had its highest expression levels in the ovary, which were 356 times those in testis, whereas LsSox9 presented higher expression in testis, which was 6 times more highly expressed than in the ovary. LsSox2 exhibited the highest expression during the morula stage, which was 20 times that of the D-shaped larvae or zygote. LsSox9 exhibited two expression peaks, one at the four-cell stage and the other at the trochophore stage, while the lowest expression was in the zygote. LsSox9 was 73 times more highly expressed in the four-cell stage than in the zygote stage. During gonadal development, LsSox2 presented the highest expression in the mature ovary, which was 756 times more highly expressed than in mature testis. LsSox9 presented higher expression in testis at the emission stage which was 6 times more highly expressed than in the ovary. These results indicate that LsSox2 and LsSox9 may play important roles in embryonic and gonadal development.

A coupled dynamical-copula downscaling approach for temperature projections over the Canadian Prairies - Xiong Zhou; Guohe Huang; Xiuquan Wang; Yurui Fan; Guanhui Cheng (Climate Dynamics, 2018)

Progress of research on urban-rural transformation and rural development in China in the past decade and future prospects - Yansui Liu; Hualou Long; Yufu Chen; Jieyong Wang; Yurui Li; Yuheng Li; Yuanyuan Yang; Yang Zhou (Journal of Geographical Sciences, 2016)

Using colour features of cv. ‘Gala’ apple fruits in an orchard in image processing to predict yield - Rong Zhou; Lutz Damerow; Yurui Sun; Michael M. Blanke (Precision Agriculture, 2012)